2016
DOI: 10.1051/0004-6361/201527967
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the extent of convective cores in low-mass stars usingKeplerdata: toward a calibration of core overshooting

Abstract: Context. Our poor understanding of the boundaries of convective cores generates large uncertainties on the extent of these cores and thus on stellar ages. The detection and precise characterization of solar-like oscillations in hundreds of main-sequence stars by CoRoT and Kepler has given the opportunity to revisit this problem. Aims. Our aim is to use asteroseismology to consistently measure the extent of convective cores in a sample of main-sequence stars whose masses lie around the mass limit for having a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 74 publications
(116 reference statements)
8
135
1
1
Order By: Relevance
“…Our seismically derived overshoot values for the best models are f ov = 0.024 and α ov = 0.32. These are in excellent agreement with the previous studies (reviewed by Aerts 2013 and the references therein), in addition to those of Stancliffe et al (2015) from fitting the global observables of nine binary systems, between 1.3 and 6.2 M e , and the seismic modeling of Deheuvels et al (2016) for F stars at the onset of convective cores. Thus, a global picture of overshoot mixing for a broad range of stellar masses is gradually emerging.…”
Section: Summary Discussion and Conclusionsupporting
confidence: 91%
“…Our seismically derived overshoot values for the best models are f ov = 0.024 and α ov = 0.32. These are in excellent agreement with the previous studies (reviewed by Aerts 2013 and the references therein), in addition to those of Stancliffe et al (2015) from fitting the global observables of nine binary systems, between 1.3 and 6.2 M e , and the seismic modeling of Deheuvels et al (2016) for F stars at the onset of convective cores. Thus, a global picture of overshoot mixing for a broad range of stellar masses is gradually emerging.…”
Section: Summary Discussion and Conclusionsupporting
confidence: 91%
“…They cautioned that some of these can lead to significant biases in the inferred efficiency of convective overshooting from stellar models. Deheuvels et al (2016) dispensed with binaries altogether and used diagnostics from asteroseismology of single stars observed by the Kepler spacecraft to estimate the extent of the extra mixing for eight relatively low-mass stars (1.3-1.5 M ) in which this was possible. These authors reported hints that α ov may depend on mass even over this narrow range.…”
Section: Introductionmentioning
confidence: 99%
“…This also applies to other stages of stellar evolution. With recent asteroseismological analyses constraining the convective cores during main-sequence evolution [92,93], a consistent picture might well emerge in the coming years.…”
Section: Resultsmentioning
confidence: 80%